On the Potential of Automated Algorithm Configuration on Multi-Modal Multi-Objective Optimization Problems - Rook, Jeroen; Trautmann, Heike; Bossek, Jakob; Grimme, Christian (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
Hardness of Multi-Objective (MO) continuous optimization problems results from an interplay of various problem characteristics, e. g. the degree of multi-modality. We present a benchmark study of classical and diversity focused optimizers on multi-modal MO problems based on automated algorithm configuration. We show the large effect of the latter and investigate the trade-off between convergence in objective space and diversity in decision space.
Keywords: configuration; multi-modality; multi-objective optimization

Tagungsbericht: „Fachdidaktische Entwicklungsforschung in der Deutschdidaktik – Gegenstandsspezifische Lernprozesse in den Blick nehmen“ (22.03.2022 bis 23.03.2022, Bergische Universität Wuppertal) - Drepper, Laura; Uhl, Benjamin (Didaktik Deutsch)
Der Bericht gibt Einblicke in die Tagung „Fachdidaktische Entwicklungsforschung in der Deutschdidaktik – Gegenstandsspezifische Lernprozesse in den Blick nehmen“. Diese fand am 22. und 23.03.2022 an der Bergischen Universität Wuppertal statt. Im Fokus der Tagung stand die Fragestellung, wie Design-Based Research als Forschungsmethode in der Deutschdidaktik eingesetzt werden kann. Hierzu wurden entsprechende Projekte sowohl unter methodologischer als auch unter fachdidaktischer Perspektive diskutiert.

Digitale häusliche Lernumgebung: Prädiktoren und Effekte elterlicher Unterstützung beim Lernen mit digitalen Medien - Bonanati, Sabrina; Buhl, Heike M.; Gerhardts, Lara; Kamin, Anna-Maria; Meister, Dorothee (Medienimpulse)

Experimental Characterization of 3D Printed Structured Metal Packing with an Enclosed Column Wall - Riese, Julia; Reitze, Arnulf; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Additive manufacturing is a promising tool for tailored solutions in chemical engineering. This applies in particular to the design of lab‐scale packed bed columns. We present experimental results to characterize a lab‐scale 3D printed structured metal packing and compare it to a conventional counterpart. The results indicate that necessary adjustments for the manufacturing process of the metal material have an influence on important operating parameters, resulting in higher specific pressure drop, slightly higher liquid holdup and lower mass transfer efficiency.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Computing generalizations of temporal \emph\(ϵ\)L concepts with next and global - Tirtarasa, Satyadharma; Turhan, Anni-Yasmin (SAC ’22: The 37th {ACM/SIGAPP} Symposium on Applied Computing, Virtual Event, April 25 - 29, 2022)

TLS-Anvil: Adapting Combinatorial Testing for TLS Libraries - Maehren, Marcel; Nieting, Philipp; Hebrok, Sven Niclas; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (31st USENIX Security Symposium (USENIX Security 22))

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Increasing the metal-to-ligand charge transfer (MLCT) excited state lifetime of polypyridine iron(II) complexes can be achieved by lowering the ligand's π* orbital energy and by increasing the ligand field splitting. In the homo- and heteroleptic complexes [Fe(cpmp)2]2+ (12+) and [Fe(cpmp)(ddpd)]2+ (22+) with the tridentate ligands 6,2’’-carboxypyridyl-2,2’-methylamine-pyridyl-pyridine (cpmp) and N,N’-dimethyl-N,N’-di-pyridin-2-ylpyridine-2,6-diamine (ddpd) two or one dipyridyl ketone moieties provide low energy π* acceptor orbitals. A good metal-ligand orbital overlap to increase the ligand field splitting is achieved by optimizing the octahedricity through CO and NMe units between the coordinating pyridines which enable the formation of six-membered chelate rings. The push-pull ligand cpmp provides intra-ligand and ligand-to-ligand charge transfer (ILCT, LL'CT) excited states in addition to MLCT excited states. Ground and excited state properties of 12+ and 22+ were accessed by X-ray diffraction analyses, resonance Raman spectroscopy, (spectro)electrochemistry, EPR spectroscopy, X-ray emission spectroscopy, static and time-resolved IR and UV/Vis/NIR absorption spectroscopy as well as quantum chemical calculations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

User Involvement in Training Smart Home Agents - Sieger, Leonie Nora; Hermann, Julia; Schomäcker, Astrid; Heindorf, Stefan; Meske, Christian; Hey, Celine-Chiara; Doğangün, Ayşegül (International Conference on Human-Agent Interaction)
Smart home systems contain plenty of features that enhance wellbeing in everyday life through artificial intelligence (AI). However, many users feel insecure because they do not understand the AI’s functionality and do not feel they are in control of it. Combining technical, psychological and philosophical views on AI, we rethink smart homes as interactive systems where users can partake in an intelligent agent’s learning. Parallel to the goals of explainable AI (XAI), we explored the possibility of user involvement in supervised learning of the smart home to have a first approach to improve acceptance, support subjective understanding and increase perceived control. In this work, we conducted two studies: In an online pre-study, we asked participants about their attitude towards teaching AI via a questionnaire. In the main study, we performed a Wizard of Oz laboratory experiment with human participants, where participants spent time in a prototypical smart home and taught activity recognition to the intelligent agent through supervised learning based on the user’s behaviour. We found that involvement in the AI’s learning phase enhanced the users’ feeling of control, perceived understanding and perceived usefulness of AI in general. The participants reported positive attitudes towards training a smart home AI and found the process understandable and controllable. We suggest that involving the user in the learning phase could lead to better personalisation and increased understanding and control by users of intelligent agents for smart home automation.
Keywords: human-agent interaction; smart homes; supervised learning; participation

Dreidimensionale Oberflächenanalyse und Topografie-Simulation additiv hergestellter Laser-Sinter Bauteile - Delfs, Patrick
Anwendungen von Laser-Sinter Bauteilen als Sichtteile sind aufgrund der vergleichsweise schlechten Oberflächenqualität sehr begrenzt. In dieser Arbeit werden dreidimensionale Kennwerte benutzt, um die Oberflächenqualität von Laser-Sinter Bauteiloberflächen und die Einflüsse aus unterschiedlichen Bereichen der gesamten Prozesskette zu evaluieren. Beispielsweise wurden objektive Kennwerte, mit deren Hilfe Orangenhaut zu identifizieren ist, und Prozessparameter, die diese deutlich vermindern, gefunden. Mittels Durchführung von haptischen Versuchen wurde das subjektive Empfinden ermittelt und konnten zu objektiven Kennwerten korreliert werden. Eine mikroskopische Betrachtung des flachen Oberflächenwinkels mit verschieden farbigen Pulvern zeigt neue Erkenntnisse zum Anschmelzvorgang von Partikeln an die Schmelze. Zur nachträglichen Glättung von Oberflächen wurden mechanische, chemische und optische Nachbehandlungsmethoden verwendet und deren Potential aufgezeigt. Eine abschließende neuartige Simulation der dreidimensionalen Topografie bildet die Grundlage für ein Programm zur automatischen und funktionsgerechten Orientierung von Bauteilen, welche am Beispiel eines realen Bauteils erfolgreich validiert wurde. Zusammengenommen zeigen die Ergebnisse, dass die richtige Wahl von Bauorientierung und Prozessparametern entscheidend für die Bauteilqualität ist und selbst eine aufwendige Nachbearbeitung eine ungeschickte Wahl derer nur schwerlich ausgleichen kann.
Keywords: Additive Fertigung; Oberflächenqualität; 3D; Topografie; Simulation; PA12; Laser-Sintern; Rauheit

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)